ADAPTASI PERUBAHAN IKLIM MELALUI PEMETAAN EKOSISTEM MANGROVE PARTISIPATIF BERBASIS KOMUNITAS DI KOTA SEMARANG - Wisnu Putra Danarto (Fakultas Teknik Universitas Cenderawasih, 2023)
Coastal areas have various potential resources, both physically, socio-economically and biologically. This situation places enormous physical and social pressure on coastal areas, increasing their vulnerability to various hazards such as storms, flood waves and tsunamis, sea level rise and land subsidence. The coastal area of ​​Semarang City is facing this threat. In a literature review conducted by researchers, apart from the imminent danger, there is also the potential for mangrove ecosystem resources around the Opak River estuary which can be used as a natural embankment to reduce the impact of coastal disasters. The aim of this research is; (1) mapping of existing mangrove ecosystems and their management; and (2) updating the Action Plan for Mangrove Ecosystem Management and updating community and local community perceptions of mangrove ecosystem services as a way to reduce the risk of coastal disasters. Obtain research materials using FGD techniques, in-depth interviews and secondary data documentation; Processing, analysis and presentation of data using qualitative research methods. Participatory mapping of the current condition of the mangrove ecosystem will be carried out to determine the level of public knowledge about the opportunities and problems of the mangrove ecosystem. The results of the participatory mapping are also used as material in focus group discussions that establish a therapeutic action plan with different options such as: B. Restoring damaged mangrove vegetation, developing ecosystem land, empowering communities to manage ecosystems, and using ecosystems as a means of transportation for ecotourism. and representative tourism. The process of developing and implementing an action plan for ecosystem management is a participatory management model which can then be developed with several other elements in research on coastal natural resource management as a means of disaster risk reduction.